2017
DOI: 10.14507/epaa.25.2761
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of predictors of history content knowledge: Implications for policy and practice

Abstract: Abstract:How and to what extent students learn history content is a complicated process, drawing from the instructional opportunities they experience; the policy prioritization of history/social studies instruction in schools; and their own cultural perspectives toward the past. In an attempt to better understand the complex inter-play among these dimensions, we examined relationships among student sociocultural characteristics, instructional exposure, and school-level variables and US History content knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 76 publications
(118 reference statements)
1
1
0
2
Order By: Relevance
“…An alternative explanation for why RDW, in the final model, no longer correlated with NAEP-US8 performance is the predictive effect of social studies testing context. Teachers working in states mandating a middle/high school social studies test, a proxy for curricular standardization, were significantly associated with increased average performance; aligning with findings in prior studies which suggest a state-level testing habitus correlates with increased achievement levels on NAEP (Fitchett et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…An alternative explanation for why RDW, in the final model, no longer correlated with NAEP-US8 performance is the predictive effect of social studies testing context. Teachers working in states mandating a middle/high school social studies test, a proxy for curricular standardization, were significantly associated with increased average performance; aligning with findings in prior studies which suggest a state-level testing habitus correlates with increased achievement levels on NAEP (Fitchett et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…Even though student demographics were not predictors of interest in this study, previous research found that student characteristics were substantially associated with performance on various NAEP assessments Fitchett, Heafner, & Lambert, 2017;J. Smith & Niemi, 2001).…”
Section: Methodsmentioning
confidence: 60%
“…The results of our study are largely consistent with the results from other disciplines that have developed models of achievement using NAEP data. Students of color, females, and students who are eligible for free or reduced-price lunch often attain significantly lower scores than their counterparts on NAEP assessments for U.S. history (Heafner and Fitchett 2015;Fitchett, Heafner, and Lambert 2017) and economics (Heafner, VanFossen, and Fitchett 2019). The same is true for students who receive language and learning accommodations and whose parents did not attend college.…”
Section: Inequality In Student Outcomesmentioning
confidence: 97%